ANALISIS PRINSIP SENI RUPA DALAM KARYA LUKIS MENGGUNAKAN TEKNIK FINGER PAINTING DI SEKOLAH DASAR - Hani Halimatusyadiah; Din Azwar Uswatun; Lutfhi Hamdani Maula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the application of art principles in the painting works of fifth-grade students at SDN Cikuda using the finger painting technique, as well as to identify the supporting and inhibiting factors during the process. The research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation of students' artwork. The findings reveal that most students were able to apply the principles of unity, balance, and dominance quite well. This is evident in the harmonious visual composition, the prominent placement of main objects, and the visual balance among elements. However, the principles of rhythm, harmony, and proportion were not yet fully mastered. Supporting factors include students’ enthusiasm, engaging teaching methods, and active guidance from the teacher. Meanwhile, the main challenges encountered were limited materials, short instructional time, and the students’ developing understanding of visual structure. Overall, the finger painting technique proved to be an effective art learning medium at the elementary level as it provides a free, enjoyable, and educational form of expression. It is recommended that art learning be further optimized through varied visual approaches and consistent practice to enhance students’ artistic understanding and skills.